Molecular Characterization and Ex Situ Conservation of Wild Grapevines Grown in the Area Around the Neolithic Settlement of Dikili Tash, Greece - Georgios Merkouropoulos; Ioannis Ganopoulos; Georgios Doupis; Erika Maul; Franco Röckel (Agriculture, 2025)
Dikili Tash is a Neolithic settlement that lies next to the ruins of the ancient city of Philippi on the north-eastern part of Greece. A recent archaeological excavation has unearthed charred grapevine pips and pressings together with two-handed clay cups, jugs, and jars that date to 4300 BC. The majority of the pips were found to be Vitis vinifera ssp. sylvestris. Natural populations of this species have been localized in the valley surrounding Dikili Tash and also on Mt Pangaion and Mt Lekani, which flank the valley. Fifty-one samples from these modern populations have been analyzed using microsatellites on twenty microsatellite loci, and a dendrogram has been constructed showing the genetic closeness of the samples analyzed. Cuttings from all the vines analyzed are currently rooted and grown in the Hellenic Agricultural Organization—DIMITRA (ELGO-DIMITRA) greenhouse facilities in Lykovryssi (Athens) with the aim to, eventually, be transplanted in the grapevine, thus establishing the first V. sylvestris ex situ conservation site in Greece.